KENALKAN PERPUSTAKAAN RUMAH POHON KEPADA ANAK-ANAK TAMAN PERUMAHAN DENGAN TEKNOLOGI VIRTUAL REALITY - Akhmadi, Akhmadi; Abdulhadi, Reza Hambali Wilman; Ismiranti, Athifa Sri; Budiono, Irwana Zulfia (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
Research says that introducing reading habits to children should start from the age of 0-2 years. A residential park is a public facility closest to a residence and is located in a housing complex. Block C Park at Pesona Ciganitri Housing RT 10, RW 12, Cipagalo Village, Bojongsoang District, Bandung Regency is a cluster complex park and has a triangular shape with an area of ​​around 300 M2. The condition of the garden, which is overgrown with trees and grass, makes reading and studying together very suitable for supporting children's activities in this housing complex. This community service activity aims to create an atmosphere of learning while playing in the park and a new experience for the children of Pesona Ciganitri Housing in trying the Virtual Reality (VR) game in the digital room of the tree house library. The introduction of VR is to increase interest in reading while playing in the park. The community service method is carried out in a sequential exploration manner, where the team conducts surveys and interviews with residents, measures land needs and designs, then socializes the results of the design and holds a soft opening to inaugurate the handover to residents. The results of the community service were inviting children to try VR in the park and parents were able to provide input at the design discussion session. The satisfaction survey shows that 100% of residents agree and are satisfied with community service activities. They also fully support physical development through invitations to become donaturs.